Natural History of the Ant Pheidole desertorum Wheeler in a Desert Grassland Habitat - Ken R. Helms (Psyche: A Journal of Entomology)
Pheidole desertorum colonies are large for the genus; the number of adult workers in established colonies ranges from 2,460–24,814. They are nocturnal during summer and are predators and scavengers on arthropods. Both minor and major workers forage, although foraging by majors appears to occur primarily when food is abundant. Young major workers may function as repletes. The adult major/minor worker ratio varies greatly among colonies; much of that variance appears explained by colony size and marturity of adult colony reproductive broods. Most colonies produce reproductives each year and colony sex ratios are extremely sex-biased. Mating season begins following summer rainfall, Males and gynes fly prior to sunrise; males form aerial swarms which gynes enter. Mating occurs on the ground, then gynes fly awy, presumably o suitable colony founding sites Colony f0udation is normally haplometrotic, although pleometrotic queen associations with workers are found.